Metabolite profiling reveals temperature effects on the VOCs and flavonoids of different plant populations - Goh, H.-H.; Khairudin, K.; Sukiran, N. A.; Normah, M.N.; Baharum, S.N. (Plant biology (Stuttgart, Germany), 2016)
Temperature is one of the key factors in limiting the distribution of plants and controlling major metabolic processes. A series of simulated reciprocal transplant experiments were performed to investigate the effect of temperature on plant chemical composition. Polygonum minus of different lowland and highland origin were grown under a controlled environment with different temperature regimes to study the effects on secondary metabolites. We applied gas chromatography–mass spectrometry and liquid chromatography time‐of‐flight mass spectrometry to identify the chemical compounds. A total of 37 volatile organic compounds and 85 flavonoids were detected, with the largest response observed in the compositional changes of aldehydes and terpenes in highland plants under higher temperature treatment. Significantly less anthocyanidin compounds and larger amounts of flavonols were detected under higher temperature treatment. We also studied natural variation in the different plant populations growing under the same environment and identified compounds unique to each population through metabolite fingerprinting. This study shows that the origin of different plant populations influences the effects of temperature on chemical composition.